Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Pada Materi Perbandingan di Kelas VII SMP Negeri 4 Medan T.A. 2016/ 2017 - Hia, Yasifati; Syafputri, Rani Sugesti (Jurnal Pendidikan Matematika dan Sains, 2017)
This study aims to improve students mathematical problem solving using problem based learning model in the comparison material in class VII SMP Negeri 4 Terrain FY 2016 / 2017. Subjects in this study were students of class VII SMP Negeri 4 Terrain FY 2016/2017 consists of eleven classes and taken two classes of class VII-4 and class VII-9 and the object of this study is to improve the ability of problem solving math students on the material ratio by applying problem based learning in class VII SMP Negeri 4 terrain TA 2016 / 2017. The research instrument used was a test, observation, interviews and documentation.This research is a classroom action research (PTK) consisting of two cycles, each consisting of two meetings. The results of this PTK is an act. Before giving the action, first administered tests the ability of the beginning and end of each cycle is given kemampan troubleshooting tests. From the analysis of data obtained by an increase in final test results problem-solving ability. The number of students who achieve mastery learning from its initial capability test 4 out of 35 students (11.43%) with the average grade 39.03. The results of data analysis in the first cycle after using problem-based learning model obtained the ability to understand the problems of students 81.08%, the level of student problem-solving abilities to plan 78.02%, the level of problem-solving ability to execute 72.25% and the rate of re-examine the problem solving abilities 52.43%, with the number of students who completed are 27 students from 37 students or 72.97% and yet achieve mastery class. The results of data analysis in the second cycle with problem-based learning model obtained the ability to understand the problems of students 82.70%, the level of student problem-solving abilities to plan 82.16%, the level of problem-solving ability to execute 80.18% and the level of problem solving ability to re-examine 67 , 29%, with the number of students who completed are 32 students from 37 students or (86.49%) that already achieve mastery classes, namely by 85%. Thus it can be concluded that by using problem-based learning model student mathematics problem solving ability can be improved